The unwicked Stepmother: the Dowager Empress Eleonora II Gonzaga as a swing vote at the Court of Vienna - Lothar Höbelt (Los Libros de la Corte.es)
The Dowager Empress Eleonora II Gonzaga was credited with great influence over her step-son Emperor Leopold I (r. 1657-1705). For that reason, she was not just courted by Venetian, French and Papal diplomats. Unusual for female members of the Casa d’Austria, even the minutes of official meetings of Austrian ministers show that she was a force to be reckoned with. However, Eleonora did not consistently favour one of the court factions. The marriage of her daughter to Polish king Michal Korybut in 1670 might have been supposed to turn her into an ‘Easterner’, willing to appease the French. Indeed, Eleonora was originally regarded as an ally by French ambassador Gremonville, but decisively turned against him in 1671/72. Ten years later, with a French threat to her native Mantua (and her own inheritance prospects in Monferrato), she once again spear-headed a drive by the pro-Spanish ‘war hawks’ against the ‘business-as-usual’ appeasers in power at the time.